Effect of beam defocusing on porosity formation in laser-MIG hybrid welded TA2 titanium alloy joints. (October 2020) - Chen, Shuling; Luo, Shixuan; Yu, Hang; Geng, Hui; Xu, Guoxiang; Li, Ruifeng; Tian, Yingtao
Graphical abstract: Abstract: The influence of defocusing distance on porosity formation during laser-MIG hybrid welding of TA2 titanium alloy joints was studied by both experimental and numerical methods. The experimental results showed that the population of porosities decreased in the welded joint when the defocusing distance increased from +6 mm to +12 mm, while other welding parameters remained unchanged. A volume of fluid (VOF) model was built in FLUENT by coupling the laser induced keyhole, MIG droplet and melt pool. The simulation results suggested the formation of porosities can be attributed to the collapse of the keyhole that can trap the open space at its bottom, thanks to the vigorous laser-material interaction. When the defocusing distance increases, the laser energy density drops and the keyhole becomes shallower leading to a weaker liquid metal vortex flow. In this case, the open space at the bottom of the keyhole could be backfilled with the surrounding liquid metal when the keyhole collapse, resulting in less porosity in the solidified weld.